Remembering the AIDS Quilt - Morris III, Charles E. (Michigan State University Press, 2011)
A collaborative creation unlike any other, the Names Project Foundation's AIDS Memorial Quilt has played an invaluable role in shattering the silence and stigma that surrounded the epidemic in the first years of its existence. Designed by Cleve Jones, the AIDS Quilt is the largest ongoing community arts project in the world. Since its conception in 1987, the Quilt has transformed the cultural and political responses to AIDS in the United States. Representative of both marginalized and mainstream peoples, the Quilt contains crucial material and symbolic implications for mourning the dead and the treatment and prevention of AIDS. However, the project has raised numerous questions concerning memory, activism, identity, ownership, and nationalism, as well as issues of sexuality, race, class, and gender. As thought-provoking as the Quilt itself, this diverse collection of essays by ten prominent rhetorical scholars provides a rich experience of the AIDS Quilt, incorporating a variety of perspectives, critiques, and interpretations.